"Presencia del virus de la Influenza aviar y enfermedad de newcastle en aves silvestres y migratorias en humedales de la provincia de el Oro" - Chamba Avila, Julio Patricio (2017)
In the Province of El Oro, 300 samples of wild and migratory bird feces were collected to determine the presence of Newcastle disease virus and Avian Influenza. For the sampling, an ARGIS academic software map was developed with the sites to be sampled, based on information from the different cantons and from the 2015 AGROCALIDAD census, where wetlands, water systems, commercial and backyard poultry production coexist. With a sample size of 300 based on the prevalence limit with a minimum prevalence less than 1% (Gonzales 1986). It was determined that the samples to be collected by area were as follows: upper area: 34 sampling points 82 samples collected, medium area: 52 sampling points 136 samples collected, lower zone: 67 sampling points 82 samples collected, collected And transported in UTM tubes to the laboratory. The samples were used to perform viral isolation in embryonated eggs of 9 - 11 days, through the hemagglutination test and inhibition of hemagglutination, analyzes performed at the University Of San Marcos De Lima, in the laboratory of Avian Pathology. 95% confidence intervals were calculated using the "R" statistical program by applying the "epiR" version 09 - 79 package, obtaining the following confidence intervals: all zones presented a prevalence lower than unity with a confidence interval of (0 - 1.19). All samples from the birds tested gave negative results for antibodies against VNC and AI, revealing that migratory and resident wild birds had not been exposed to the virus and that at the time of sampling they were not excreting the virus. Virus and that they could not constitute in a reservoir, or that the amount of viral RNA both of NC and IA was minimal, that could be lost in the transport and conservation of the sample or in its defect could not be detected by the isolation And the HI test, which is why molecular tests are recommended to detect minimal amounts of RNA such as RT-qPCR. Key Words: Isolation, Avian Influenza, Newcastle, Viruses, and Risk.